Law and logic: A deductive criterion for determination of truth value of evidence in civil and administrative procedures – Part I - Paskalev, Emilian; Latinov, Evgeni (Law Journal of New Bulgarian University, 2023)
The study examines the possibility of applying a deductive logical criterion for determination of the truth value of evidence in civil and administrative procedures. Part I points out types of evidence and facts with ex lege definite truth value according to current legislation in Bulgaria. It reviews the opportunity evidence without such ex lege definite truth value to be subjected to verification using the proposed deductive criterion. It is also argued that in the criterion’s application as premises evidence and facts with ex lege definite truth value should be involved in order to guarantee the truth value of the conclusions. The study provides a detailed review of the propositional logic apparatus involved. Part II reviews the deductive method applied – the method of natural deduction. The application of the deductive criterion in determining the truth value of evidence in an example from legal practice is also shown. At the end the method of natural deduction is applied to a particular kind of proof – based only on circumstantial evidence with ex lege definite truth value. The study concludes with summary of the advantages and limitations of the application of the deductive criterion, some new areas of application of deductive logic in civil procedure are reviewed and some open research issues are pointed.